PAI TEACHERS' PERSPECTIVES AT MAN 1 MANDAILING NATAL ON MBKM: PHILOSOPHY, METHODOLOGY, AND IMPLEMENTATION - Amru Abdul Wadud; Anhar (PT Rahis Cendekia Indonesia, 2024)
Study This aim For understand The views of Islamic Religious Education (PAI) teachers at State Islamic Senior High Schools (MAN) and Private Islamic Senior High Schools (MAS) regarding the Independent Learning Independent Campus (MBKM) program , with focus on aspects philosophy , methodology and implementation in context Islamic Education . Approach qualitative used in study this , with collect data through interview deep from Several Islamic Religious Education teachers at various MAN/MAS in Indonesia. Findings study show that Islamic Education teachers view MBKM philosophy as A initiatives that give freedom and flexibility in the learning process , enabling student For Study in accordance interest and potential they . In case methodology , they confess challenge in apply a more approach open and based experience , such as outdoor learning​ class . Although Thus , the implementation of MBKM in the eyes Islamic Religious Education lessons are still limited , especially related with learning based projects and collaborations between institution education . PAI teachers have an opinion that even though MBKM has potential For increase quality education , there is need will more training and support​ intensively so that the methods and curriculum applied in accordance with characteristics religious education . Research This give understanding more carry on about how MBKM can adapted in Islamic religious education in madrasas, with consider religious values and wisdom local needs​ maintained .